Crystal phase dependent metal-support interactions in Pt/SO42--ZrO2 catalysts for hydroconversion of n-alkanes - Grau, Javier Mario (2004)
In order to elucidate the influence of the crystal structure of zirconia on the properties of the metallic and acid function of Pt/SO42−-ZrO2, catalysts with different zirconia crystal phases were synthesized, fully tetragonal, fully monoclinic, and with a mixture of the tetragonal and monoclinic phases. Their catalytic properties were studied in the metal-catalyzed reaction of cyclohexane dehydrogenation (300 °C, 0.1 MPa, , H2/C6H12=30), the acid-catalyzed isomerization of n-butane (350 °C, 0.1 MPa, , H2/C4H10=6), and the bifunctional hydroconversion of n-octane (300 °C, 1.5 MPa, , H2/C8H18=6). TPR, XRD and FTIR of chemisorbed CO were also used in order to characterize the catalysts. The results showed a strong influence of the crystal phase on the activity of the acid function. A less marked effect was found for the metal-catalyzed reaction. An opposite relation between the two functions was seen with respect to this crystal structure influence. Among the sulfated catalysts, monoclinic Pt/SO42−-ZrO2 had the lowest activity in n-C4 isomerization and the highest activity in cyclohexane dehydrogenation. Tetragonal Pt/SO42−-ZrO2 catalysts were the most active in isomerization of n-butane. They had the lowest activity in cyclohexane dehydrogenation and their metal properties were negligible. They were also the most active in n-C8 conversion, producing mainly i-C4. Monoclinic catalysts had low cracking activity and produced mainly isooctane. Mixed phase catalysts had an intermediate behavior. While S poisoning of Pt was present as a uniform effect on all sulfated catalysts, the metal–acid behavior and the different Pt properties could be explained by a metal–support interaction between tetragonal SO42−-ZrO2 and Pt. The Pt–support interaction was analyzed both with a model of Pt particles encapsulation and a model of electron depletion. The electronic deficiency of Pt particles supported on SO42−-ZrO2 was evident in the shift of the IR bands of adsorbed CO. Further experimental work is however needed to get conclusive evidence about the nature of the Pt–support interaction.